The effects of celebrity endorsement on brand reputation and consumer behaviour among UTAR students - Foo, Nicolette Ni En (2024)
Celebrity endorsement has emerged ever since the industry became highly competitive, brands use it as a marketing strategy to maintain their reputation and an influence on consumer behaviour. While it is a prominent and efficacious tool, the actual impact can be caused by celebrity marketing is still yet to be comprehensively studied, particularly when celebrities seem to be relatively approachable as the evolution of technology has developed from television to social media where it fosters engagement between celebrities and their followers. Therefore, this research aims to study the effect of celebrity endorsement on brand reputation and consumer behaviour among university students. In this research, a quantitative approach will be employed with the help of Google Form to survey a total of 104 students in UTAR. Social Identity Theory was employed to study how individuals extend their identity by associating with celebrity endorsements on brands and the way celebrity endorsements reinforce customer loyalty by providing a sense of belonging to the brand’s community, which, in turn, influences consumer behaviour. The results show that brand reputation and consumer behaviour are indeed affected by celebrity endorsement to different levels, and that it can bring positive and negative impact. The result also indicates that brands shall be authentic and true to themselves to be sustained in the industry, not mentioning that appointing the right celebrity for brand marketing could be one of the most crucial steps for long-term success.